PENGARUH MEDIA SMART BOX TERHADAP HASIL BELAJAR IPAS PADA SISWA KELAS IV SD - Lubis, Sri Lewi Giovani; Nasution, Yusra; Siregar, Tiarnita Maria Sarjani Br.; Tambunan, Husna Parluhutan; Sembiring, Masta Marselina (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to determine the effect of using smart boxes on students' science learning outcomes in the Indonesiaku Kaya Budaya (My Indonesia is Rich in Culture) material in grade IV of SDN 107443 Kampung Taiwan. This study is a quantitative study using a quasi-experimental method. The research population consisted of all 30 fourth-grade students at SDN 107443 Kampung Taiwan, divided into two classes. Random sampling was used to determine the research sample, namely 15 students in class IV-A as the experimental class and 15 students in class IV-B as the control class. The results of data analysis showed that students' IPAS learning outcomes were influenced by the use of smart box learning media. Students in the control class obtained an average learning outcome score of 64.66, while students in the experimental class obtained an average score of 78.66. Based on the t-test results at a significance level of 0.05, with a t-value greater than the t-table (3.009 > 2.048), it can be concluded that there is a difference in student learning outcomes between the two research classes. Thus, smart box learning media has an effect on the learning outcomes of fourth-grade students at SDN 107443 Kampung Taiwan.